OPTIMISATION OF AVICENNIA MARINA HEARTWOOD EXTRACT NANOEMULSION USING BOX–BEHNKEN DESIGN: FORMULATION CHARACTERISTICS AND ANTIFUNGAL EVALUATION - SYAHPUTRA, HAFID; REVENY, JULIA; DEWI PANJAITAN, NOVARIA SARI; BR SILAEN, MIKHA RIAMA (International Journal of Applied Pharmaceutics, 2026)
Objective: This study aimed to develop a practically suitable Avicennia marina heartwood extract nanoemulsion and evaluate its physicochemical characteristics, stability, and anti-dandruff activity. Methods: The heartwood extract was obtained by maceration using 96% ethanol, followed by phytochemical screening. Nanoemulsion formulations were developed using Response Surface Methodology with a Box–Behnken Design to investigate the effects of virgin coconut oil (VCO), Tween 80, and sorbitol on viscosity and particle size. The extract concentration was fixed at 0.5%, and one blank formulation was used as a control. Physicochemical evaluation included viscosity, particle size, pH, homogeneity, and stability testing at room temperature. Anti-dandruff activity was assessed against Pityrosporum ovale using the disk diffusion method on Potato Dextrose Agar. Results: The viscosity model was statistically significant (p < 0.05), with Tween 80 and its interaction with VCO identified as dominant factors influencing viscosity. Although the particle-size model did not reach statistical significance, several formulation variables showed meaningful effects on droplet size. A formulation consisting of 1.13% VCO, 15.96% Tween 80, and 2.18% sorbitol produced a nanoemulsion with a viscosity of 1.12 mPa·s and an experimentally confirmed minimal particle size of 51.42 nm within the studied Design space. The selected formulation remained physically stable during storage and exhibited strong anti-dandruff activity, with an inhibition zone diameter of 14.63 mm against P. ovale. Conclusion: This study demonstrates that a practically stable nanoemulsion of A. marina heartwood extract can be achieved through formulation-guided optimisation, yielding favourable physicochemical properties and effective anti-dandruff activity, thereby supporting its potential application in topical anti-dandruff formulations.